Hydrogels of enzymatically modified dextrin - Carvalho, Joana (2005)
Dextrin is a glucose-containing saccharide polymer linked by α-(1→4) D-glucose units and is produced by partial hydrolysis of starch. Hydrolysis can be accomplished by the use of acid, enzymes, or by a combination of both. In this work, the Bacillus subtilis protease Proleather FG-F catalyzed the transesterification of the soluble polysaccharide with vinyl acrylate (VA), using anhydrous dimethylsulfoxide (DMSO) as reaction medium. Different degrees of substitution (DS, defined as the amount of acrylate groups per 100 glucopyranose residues) ranging from 11 to 19 % were achieved by controlling the molar ratio of VA to dextrin. Dextrin derivatized with VA (dextrin-VA) was characterized by gel permeation chromatography. Gels were obtained by free radical polymerization of aqueous solutions of dextrin-VA with different degrees of substitution and monomer concentration. Swelling experiments have been performed in order to determine the gel pore sizes. Specific physical properties, as degradation behaviour were also evaluated. These hydrogels are being developed as scaffold materials for bioactive molecule and cell delivery, tissue engineering and a variety of other biomedical applications.